Chronic Effects of Pediatric Ear Infections on Postural Stability. (15th February 2021) - Sabir, Ohud A.; Johnson, Eric G.; Hafiz, Ammar E.; Nelson, Rhonda N.; Hudlikar, Mitali; Sheth, Isha; Daher, Noha S.
Abstract : Background . Ear infections in children often cause abnormal postural stability. However, the long-term effects of recurrent ear infections on postural stability have not been investigated. Purpose . The purpose of this study was to examine the long-term effects of multiple ear infections on pediatric postural stability. Methods . Forty children aged 10-12 years were divided into two groups (18 participants with a history of tympanostomy tubes and/or 3 or more ear infections prior to age five and 22 participants without a history of tympanostomy tubes and/or 0-2 ear infections prior to age five). Computerized Stability Evaluation Test (SET) and noncomputerized postural stability were measured for all participants. Results. A significant difference was found in median postural stability scores in the SET during a tandem stance on an unstable surface between the two groups (median (minimum, maximum) of 9.1 (1.4, 11.4) versus 5.8 (1.7, 12.8), p = 0.04 ). In addition, there was a significant difference in median Pediatric Balance Scale scores between participants with versus without ear infection (54 (47, 56) versus 56 (55, 56), p = 0.001 ). Conclusions. Results suggest that children ages 10-12 with a history of tympanostomy tubes and/or 3 or more ear infections prior to age five have decreased postural stability.